Rational Addiction to News? : Habit Formation and Print Media Usage - Ralf Dewenter (Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2003)
Quarterly data of magazine circulation are used to analyse the consumption behaviour of the readers of German popular magazines in a panel framework using OLS,2SLS and generalized method of moments techniques,in order to test the rational addiction hypothesis in respect with goods without any biological dependency.
urn:nbn:de:gbv:705-opus-1304
Keywords: L89; D12; C23; 330; Rational Addiction; Habit Formation; Print Media; Panel Data; Medienverhalten; Zeitschrift; Sucht; Rationales Verhalten; Schätzung; Deutschland